Broadband circularly-polarised antenna consisting of four notch slot radiators - Ren, H. (2013)
A broadband antenna consisting of four notch slots is proposed to generate circularly-polarised radiation. Wide bandwidth is achieved by using notch slots operating in the double-resonance range. A separate feeding network is designed to meet the requirement of sequential rotation excitation for the four slots maintaining a corresponding phase difference of 908 between adjacent slots. Simulated and measured results are presented to demonstrate the high directivity and wide bandwidth of the circularly-polarised antenna. The designed antenna exhibits a bandwidth from 4.9 to 6.1GHz for both |S11|≤ 210 dB and AR≤ 3 dB, which is 21% of the centre frequency of 5.5GHz. Peak gain at 5.5 GHz is 7.6 dBic along the zenith direction, with less than 1dB gain variation within the operating bandwidth.